Effect of the winter legume as cover crop on the yield and n response of a no till corn - Ernst, O. (Agrociencia Uruguay, 2006)
When the crop system includes a rotation with perennial grass and legumes pastures, there is an N income through symbiotic fixation that on average exceeds 100 kg ha-1 year-1. Planting an annual legume between two consecutive summer crops would allow the incorporation of additional N in the system, during the otherwise unproductive period between the harvest of the first crop and the planting of the second one. The effect of the inclusion of a legume (Trifolium alexandrinum) as cover crop on the N input and corn grain yield in a cornfallow-corn sequence was studied. Treatments were arranged in a factorial design of cover treatments (with cover crop –CC- and without cover crop–SC-) by N treatments added as urea at corn planting (0, 20, 40 y 60 kg ha-1). There was no difference in soil water availability between CC and SC treatments. Soil N-NO3 - availability, N uptake, and dry matter production at growth stages V6 and R1 were significantly higher in CC. The apparent recovery efficiency of N fixed by CC increased from 13% at V6, to 24% at R1, and 47% at harvest. The N fertilizer equivalent was 24 kg ha-1 , and the N apparent utilization was 36%.